An experience of cooperative learning in university education: the portfolio - Cerezo Máiquez, Mari Carmen; Castillo Reche, Irina Sherezade; Sánchez Castro, Susana; Suárez Lantarón, Belén (Revista Complutense de Educación, 2025)
University teaching is looking for new methodologies that favour the development of the competences required of students in today's society. In this work, which is part of a teaching innovation project, we wanted to combine cooperative learning with the use of audiovisual materials in order to show students real-life situations that encourage reflection, autonomy and participation through individual and group work in order to achieve their own learning. The learning process is carried out under the supervision of the teacher, who favours and encourages situations and tasks in order to develop competences. A qualitative methodology was used, focusing the study on the evaluations collected in the students' portfolios. The participants were 707 students from two universities (Extremadura and Murcia), belonging to different bachelor's and master's degree programmes. The results show a positive assessment of the methodology based on cooperative learning situations and a positive effect on the development of essential competences for future teachers.
Keywords: cooperative learning; university teaching; audiovisual materials; portfolios